Penyuluhan Persiapan ASI Ekslusif pada Ibu Hamil Di Desa Bori Kamase Kecamatan Maros Baru Kabupaten Maros - Sitti Nurana; Sitti Hadriyanti Hamang (PT.Mantaya Idea Batara, 2021)
Lactation Preparation In pregnancy is an effective activity to increase exclusive breast milk coverage and early breastfeeding initiation (IMD). Participants are prioritized pregnant women as well as posyandu cadre mothers. The success of exclusive breastfeeding depends heavily on lactation preparation during pregnancy, often found in the field, the fundamental reasons mothers do not give breast milk to their babies are, (1) Breast milk has not come out on the first day, so given Formula Milk while waiting for mother's breast milk, (2) Breast milk is still a little, and (3) Nipples sink. Some of the above reasons can be anticipated in pregnancy at the age of aterm pregnancy, namely by explaining to the mother about the lactation process, the baby's need for breast milk in the early stages of birth and breast care at the age of aterm pregnancy, as well as the provision of knowledge about balanced nutrition that can be consumed during pregnancy to help increase the production of breast milk in the nifas / or lactation period, However, this group is open to others who have similar interests, such as husbands, or families who will support and accompany the mother during pregnancy until the process of breastfeeding later. Through the extension of lactation preparation given, it is expected that pregnant women can prepare the lactation process since pregnancy as an effort to successfully breastfeed exclusively.